Search for universal extra dimensions in ppbar collisions - De Souza Santos, Angelo [UNESP] (My University, 2013)
Models that predict the existence of extra spatial dimensions have been studied since the beginning of the 20th century. These models can incorporate gravity in the framework that describes the other interactions and they can present a number of interesting features such as a dark matter candidate. The consequences of the Universal Extra Dimensions (UED) model is explored by searching for the production of Kaluza-Klein particles whose decay chain leads to signature µ±µ± + jets + E/T. Analyzing the data set corresponding to an integrated luminosity of 7.3 fb- 1, collected by the DØ detector at a pp¯ collider at a center of mass energy of 1.96 TeV, no excess was observed and a lower limit was set on the compactification scale of R- 1 > 260 GeV in the model. This is the first study to impose a direct limit on the minimal UED model.